PENERAPAN MODEL PROJECT BASED LEARNING DALAM MENINGKATKAN KOMUNIKASI MATEMATIS SISWA SEKOLAH DASAR - Maiyona Ovartadara; Firman; Desyandri (STKIP Subang, 2022)
The Project Based Learning (PjBL) model increases various students' mathematical communication. The purpose of this study was to determine the PjBL model in improving various mathematical communication skills. Mathematical communication is one of the abilities that must be owned by every student with various interests in learning mathematics. Mathematical communication is the ability to communicate related to each class including writing activities, interpreting, evaluating ideas, and providing mathematical information, conveying messages containing mathematical material. Data collection techniques were obtained from literature review studies on library research or descriptive document studies (Library Research) from various types of documents that support the research theme, namely laws, books, journals and articles. Data analysis techniques consist of content analysis methods, which focus on the positive content and characteristics of a media. research shows that PjBL forms an innovative learning model in a learning and is student-centered using projects as a learning medium so as to improve students' communication skills, especially when communicating so that students can carry out activities actively in solving various problems to produce products that have value. However, PjBL can be responsible for having tolerance for each individual because it is mandatory for school and has high self-confidence, but has limitations with elementary school students as learning materials that influence PjBL and obtain technology assistance on computers for learning materials with different classes .